Caracteriza??o de canal sem fio com correlator deslizante - Scudeler, Lu?s Ant?nio Ribeiro (2016)
The research and development of wireless communications systems are always preceded by the channel characterization through which the signal will be transmitted. Such characterization covers the time, frequency and space domains, and can be stochastic, empirical, deterministic or a combination of these. It provides subsidies for the channel to be modeled and the system is scaled so as to enable communication with the possible channel adversities, and can also provide data for the predictive models coverage elaboration. It is common for channel models to be constructed with the aid of field measurements, which are obtained by probing techniques which process the received signal from the transmission of a known probing signal. The sliding correlator is one of the most used probing techniques, allowing to obtain the stochastic information that will characterize the channel. This work deals with the theoretical foundations that allow the understanding of sliding correlator as well as the procedure of analysis of measures simulated by the sliding correlator for the stochastic characterization of channel